Penerapan Pembelajaran Daring Materi Teks Berita Melalui Live Instagram Pada Masa Pandemi Covid-19 Kelas VIII SMP Negeri 40 Samarinda - Al Baghdadi, Nur Syifa Rahmah; Hudiyono, Yusak; Rokhmansyah, Alfian (Universitas Mulawarman, 2021)
This research was conducted at SMP Negeri 40 Samarinda in the 2020/2021 academic year, aiming to describe the application of online learning of news text material through Live Instagram that has been carried out by researchers. Researchers conducted research on junior high school students because the current condition of using Instagram is not only used by adults. But, also among children and adolescents. This Instagram application has become much in demand by children and teenagers because it has unique features in making videos or photos and being able to see the latest news. By having unique features students or students choose Instgaram as the trendy application at this time. In this online learning, researchers use the Instagram application because it has interesting features that can provide new experiences for teaching and learning activities with students. One of the interesting features in the Instagram application used by researchers is Live Instagram. The formulation of the problem raised in this study is the implementation of learning through Instagram media, the obstacles that occur in online learning and the researchers' efforts to overcome the problems of online learning through Instagram media. To achieve these objectives, researchers used qualitative research. Data were collected using interview techniques, document studies and questionnaires. The results of the study show: 1) The implementation of online learning of news text materials through Instagram media, 2) the obstacles that occur in online learning of news text materials through Instagram media, 3) the efforts made to overcome the problems of online learning through Instagram media.